A Simple Method for Establishing Adherent Ex Vivo Explant Cultures from Human Eye Pathologies for Use in Subsequent Calcium Imaging and Inflammatory Studies - Sofija Andjelic; Xhevat Lumi; Zoltán Veréb; Natasha Josifovska; Andrea Facskó; Marko Hawlina; Goran Petrovski (Journal of Immunology Research)
A novel, simple, and reproducible method for cultivating pathological tissues obtained from human eyes during surgery was developed using viscoelastic material as a tissue adherent to facilitate cell attachment and expansion and calcium imaging of cultured cells challenged by mechanical and acetylcholine (ACh) stimulation as well as inflammatory studies. Anterior lens capsule-lens epithelial cells (aLC-LECs) from cataract surgery and proliferative diabetic retinopathy (PDR) fibrovascular epiretinal membranes (fvERMs) from human eyes were used in the study. We hereby show calcium signaling in aLC-LECs by mechanical and acetylcholine (ACh) stimulation and indicate presence of ACh receptors in these cells. Furthermore, an ex vivo study model was established for measuring the inflammatory response in fvERMs and aLC-LECs upon TNFα treatment.